2012
DOI: 10.1002/adsc.201100028
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐Reactivity Studies of Simple 4‐Hydroxyprolinamide Organocatalysts in the Asymmetric Michael Addition Reaction of Aldehydes to Nitroolefins

Abstract: A series of simple 4-hydroxyprolinamides was synthesised and they were found to act as organocatalysts for the asymmetric conjugate addition of aldehydes to nitroolefins in excellent yields (98%), with complete diastereoselectivity (99:1, syn:anti) and enantioselectivity (98% ee for syn). Furthermore, the use of low catalyst loadings (5 mol%) and a low aldehyde molar excess (1.5 equivalents) were achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The authors suggested a transition state model organized by a network of hydrogen bonding interactions (Figure 2), in which the amide acts as bulky substituent and the better enantioselectivity of catalyst 3 with respect to 2 could derive from the additional stereocenter. The same asymmetric conjugate addition was investigated in 2012 by Kelleher's research group, which proposed a series of 4-hydroxyprolinamides (Scheme 2b) to examine the impact of the 4-hydroxy and the 2-methyl groups on the enantioselectivity of the prolinamide organocatalysts [32]. The synthetic route started with the α-methylation of the fully protected trans-4-hydroxyproline, followed by the diastereoisomers separation, the usual steps for the amide synthesis, and the 4-hydroxy-deprotection (Scheme 2a).…”
Section: Of 67mentioning
confidence: 98%
See 3 more Smart Citations
“…The authors suggested a transition state model organized by a network of hydrogen bonding interactions (Figure 2), in which the amide acts as bulky substituent and the better enantioselectivity of catalyst 3 with respect to 2 could derive from the additional stereocenter. The same asymmetric conjugate addition was investigated in 2012 by Kelleher's research group, which proposed a series of 4-hydroxyprolinamides (Scheme 2b) to examine the impact of the 4-hydroxy and the 2-methyl groups on the enantioselectivity of the prolinamide organocatalysts [32]. The synthetic route started with the α-methylation of the fully protected trans-4-hydroxyproline, followed by the diastereoisomers separation, the usual steps for the amide synthesis, and the 4-hydroxy-deprotection (Scheme 2a).…”
Section: Of 67mentioning
confidence: 98%
“…The synthetic route started with the α the fully protected trans-4-hydroxyproline, followed by the diastereoisom the usual steps for the amide synthesis, and the 4-hydroxy-deprotection ( coupling with N,α-dimethylbenzylamine provided the N-methylated low yields, due to the hindered nature of both of the coupling partners removal proved to be problematic due to the high aqueous solubility of t comparison, the analogous simple 4-hydroxy NH and N-methyl prolina pared in a similar manner. The application of all of the catalysts in the m addition showed that: (i) the cis relative position of the 4-OH was detrim methyl amide, (ii) the removal of the α-methyl group provided improved simplest hydroxyprolinamides 6c and 6d gave excellent performance, an The same asymmetric conjugate addition was investigated in 2012 by Kelleher's research group, which proposed a series of 4-hydroxyprolinamides (Scheme 2b) to examine the impact of the 4-hydroxy and the 2-methyl groups on the enantioselectivity of the prolinamide organocatalysts [32]. The synthetic route started with the α-methylation of the fully protected trans-4-hydroxyproline, followed by the diastereoisomers separation, the usual steps for the amide synthesis, and the 4-hydroxy-deprotection (Scheme 2a).…”
Section: Of 67mentioning
confidence: 99%
See 2 more Smart Citations